Non‐destructive damage detection on welded threaded bolts based on electromechanical impedance spectra. Issue 2 (1st September 2021) - Sahm, Daniel; Pak, Daniel; Fritzen, Claus‐Peter; Dreisbach, Anna‐Lena; Dietrich, Gerhard; Yokaribas, Volkan
Abstract: Within a research project carried out at the Department of Civil Engineering and the Department of Mechanical Engineering of the University of Siegen, a new monitoring method for non‐destructive damage detection on bolts was developed and tested according to its applicability on real life structures. The so‐called EMI‐method is based on the measurement of electromechanical impedance spectra, which change with varying structural states and thus allow for a condition assessment. Structures vibrate in a combination of their natural modes, which can provide information about their structural condition. Their modal characteristics are system‐inherent quantities and are governed by geometry, system stiffnesses and mass allocation. If a system parameter changes, e.g. the bending stiffness of a bridge, this is reflected in the vibration analysis and the modal characteristics. To identify the modal characteristics of civil engineering structures, these are excited and the system response is measured. This principle is also used for damage detection by means of electro‐mechanical impedance spectra (EMI). The observed system‐inherent quantity is the frequency‐dependent mechanical impedance Zs(ω) of the structure. The method is based on the idea that the mechanical impedance of a structure or component to be measured changes as a result of damage (or loss of prestress in the case of bolts) and thus these changes can be detected. In the project, investigations were carried out on steel plates with orthogonally welded threaded bolts, which are used, for example, as fasteners for rail supporting points on bridges. Research objectives were on one hand the detection of the prestress stage and on the other hand the detection of fatigue damage in the weld seam. Within the scope of the project, it has been investigated to what extent a change of the prestressing load can be reliably detected by means of the EMI method. Furthermore, the influence of damage to the bolt on the impedance spectra was investigated.